2018
DOI: 10.1002/jcb.27085
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of proteomics‐delineated and metabolomics‐delineated hepatic metabolic responses to (−)‐hydroxycitric acid in chick embryos

Abstract: (−)‐Hydroxycitric acid [(−)‐HCA] is widely used as a nutritional supplement to control body weight and fat accumulation in animals and humans, whereas the underlying biochemical mechanism is unclear. Broiler chicken was used as a model for studies of obesity due to its natural hyperglycemia and being insulin resistant. The current study aimed to obtain a systematic view of serum metabolites and hepatic proteins and well understand the mechanism of hepatic metabolic response to (−)‐HCA treatment in chick embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Recently, our laboratory found that (-)-HCA treatment significantly increased the aldehyde dehydrogenase 3 family member A2 (ALDH3A2) expression in chicken embryos (Peng, He, Li, Li, & Ma, 2018). ALDH3A2 is a classical target gene of peroxisome proliferatoractivated receptor α (PPARα); and PPARα plays a key role in regulation of cellular lipid and energy metabolism (Vega, Huss, & Kelly, 2000).…”
mentioning
confidence: 99%
“…Recently, our laboratory found that (-)-HCA treatment significantly increased the aldehyde dehydrogenase 3 family member A2 (ALDH3A2) expression in chicken embryos (Peng, He, Li, Li, & Ma, 2018). ALDH3A2 is a classical target gene of peroxisome proliferatoractivated receptor α (PPARα); and PPARα plays a key role in regulation of cellular lipid and energy metabolism (Vega, Huss, & Kelly, 2000).…”
mentioning
confidence: 99%
“…Importantly, our recently surprising discovery was that GPI protein level was markedly enhanced in chicken embryos after treatment with (−)-HCA. 21 GPI is an essential enzyme in glycolytic and gluconeogenic processes that catalyzes reversible isomerization. 22 This study indicated that in chicken embryos, pretransfection with sh2-GPI had reversed the suppressing effect of (−)-HCA on lipid droplet and triglyceride contents.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It has been widely proved that glucose metabolism is closely related to lipid metabolism in the body, and acetyl-CoA is a key factor in the transformation of glycolipid metabolites. Importantly, our recently surprising discovery was that GPI protein level was markedly enhanced in chicken embryos after treatment with (−)-HCA . GPI is an essential enzyme in glycolytic and gluconeogenic processes that catalyzes reversible isomerization .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations